2019
DOI: 10.1007/s11164-019-04001-0
|View full text |Cite
|
Sign up to set email alerts
|

An EPR characterisation of stable and transient reactive oxygen species formed under radiative and non-radiative conditions

Abstract: Electron paramagnetic resonance (EPR) spectroscopy is the ideal method of choice when detecting and studying the wide variety of paramagnetic oxygen-centred radicals. For simple diatomic radicals, such as the superoxide (O 2 −) or peroxy (ROO •) species, the CW EPR profile (in particular the g-values) of these species can appear similar and indeed indistinguishable in some cases. Experiments using 17 O-enriched oxygen, revealing a rich 17 O hyperfine pattern, are therefore essential to distinguish between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…[50]. On the other hand, titanium(III), due to a positive spin-orbit coupling constant, shows EPR signals at even lower g-values, below 1.99 [48][49][50][51][52]. This approach makes it possible to identify the presence of ROS of the type O 2 − and O − in PCL + (2) samples (Table 5).…”
Section: Discussionmentioning
confidence: 95%
“…[50]. On the other hand, titanium(III), due to a positive spin-orbit coupling constant, shows EPR signals at even lower g-values, below 1.99 [48][49][50][51][52]. This approach makes it possible to identify the presence of ROS of the type O 2 − and O − in PCL + (2) samples (Table 5).…”
Section: Discussionmentioning
confidence: 95%
“…In principle the observed pattern could also be due to the simultaneous presence of two distinct adsorption sites with different degree of metalto-oxygen electron transfer. Recent analysis [65] have however demonstrated that there is a unique site where the superoxide adsorbs with a low-symmetry structure and an inequivalent electron spin density distribution over the adduct. The reason of such non-equivalency is not yet clear.…”
Section: Ionic Bonding In Adsorbed Superoxide -Epr Features and Magnetic Tensorsmentioning
confidence: 99%
“…Several examples are provided, which document well selective oxidation reactions involving the O2or Ointermediates that are operating at low temperatures in catalytic gas-solid [84] and catalytic/photocatalytic solid-liquid systems in particular [85] EPR technique has often been applied to monitor surface reactions of oxygen species, but its applicability is limited to studies of radicals in the low temperature processes. Since most of ROS are unstable in nature, it is usually difficult to monitor directly their behavior at higher temperatures where they appear as transient intermediates [65].…”
Section: Reactivity Of Surface Anion-radical Oxygen Speciesmentioning
confidence: 99%
See 2 more Smart Citations